2007
DOI: 10.1029/2007gl029756
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of NO3 on soot and pyrene surfaces

Abstract: [1] The reaction of NO 3 with methane soot, hexane soot, and solid pyrene was investigated using a flow tube reactor. The uptake of NO 3 on fresh soot was fast (uptake coefficient >0.1). Based on this result and an assumed density of reactive sites on soot, the time to process or oxidize 90% of a soot surface in the atmosphere would take only approximately five minutes. This suggests that NO 3 chemistry can rapidly oxidize soot surfaces under atmospheric conditions. After exposing soot films to NO 3 for approx… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
60
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(60 citation statements)
references
References 31 publications
0
60
0
Order By: Relevance
“…According to eq 3, the uptake coefficients for NO 3 radicals on BaA, Ch, Py, 1-NP, and 1-OHP particles are 2.4, 1.5, 3.1, 0.5, and 4.8, respectively, which are much larger than the reported data. 12,27 Lambe et al 44 reported that evaporation followed by gas-phase oxidation was the main reason resulting in the uptake coefficients greater than unity observed in their experiment. In this experiment, the vapor pressures of the 4-ring PAHs are less than 6 × 10 −4 Pa and their gas-phase reaction rates with NO 3 radicals are on the order of 10 −17 − 10 −16 cm 3 ·molecule −1 ·s −1 .…”
Section: ■ Results and Discussionmentioning
confidence: 86%
“…According to eq 3, the uptake coefficients for NO 3 radicals on BaA, Ch, Py, 1-NP, and 1-OHP particles are 2.4, 1.5, 3.1, 0.5, and 4.8, respectively, which are much larger than the reported data. 12,27 Lambe et al 44 reported that evaporation followed by gas-phase oxidation was the main reason resulting in the uptake coefficients greater than unity observed in their experiment. In this experiment, the vapor pressures of the 4-ring PAHs are less than 6 × 10 −4 Pa and their gas-phase reaction rates with NO 3 radicals are on the order of 10 −17 − 10 −16 cm 3 ·molecule −1 ·s −1 .…”
Section: ■ Results and Discussionmentioning
confidence: 86%
“…However, for γ (NO 3 )>0.1, our observations represent an upper limit for γ (N 2 O 5 ). While it is unlikely that γ (NO 3 ) is uniformly greater than 0.1, recent laboratory measurements suggest that γ (NO 3 ) could be large (γ (NO 3 )>0.1) on fresh soot (Gross and Bertram, 2008;Mak et al, 2007). By routinely shifting the N 2 O 5 -NO 3 ratio to higher NO 3 , via reducing NO 2 in the source, our approach can theoretically elucidate both N 2 O 5 and NO 3 reactivity on particles.…”
Section: No 3 Reactivitymentioning
confidence: 97%
“…19 Although a mechanism has been recently suggested based on the gas-phase chemistry of PAHs with the NO 3 radical, specic markers for the radical-initiated isomer products (2-nitrouoranthene and 2-nitropyrene) were not observed during the heterogeneous chemical processes. 18,20,21 Ringuet et al reported the rst observation of the heterogeneous formation of 2-nitropyrene from particulate pyrene oxidation in the presence of O 3 /NO 2 , questioning its use as an indicator of NPAH formation in the gaseous phase. 22 Thus, the reaction mechanism of heterogeneous nitration has not been unequivocally identied.…”
Section: Introductionmentioning
confidence: 99%
“…18,19,21 To explore whether this problem of blocking reaction sites has a signicant impact on the heterogeneous reactions that occur on the PAH particle surface, we conducted an in-depth investigation of the heterogeneous oxidation of suspended pyrene (PY) …”
Section: Introductionmentioning
confidence: 99%